Influence of Material Parameters on Martensitic Transformation and Its Sensitivity Analysis. Issue 7 (29th April 2019) - Li, Chang; Gao, Jingxiang; Yu, Zhibin; Han, Xing
Abstract : Accurate acquisition of the microscopic representation of the martensite transformation process is the key to obtaining the best performance of the material, it is of great significance in the field of quenching of iron‐based materials and material design. The martensite transformation process is affected by a variety of material parameters, quantitative analysis of the influence degree, and sensitivity of various parameters on martensite transformation is the key to accurately grasp the transformation mechanism of martensite. This paper combines the phase‐field with the finite element method, a mathematical model for the transformation of martensite from metastable to steady state is established and the model is solved. Accurately reveal the law of energy field variation during martensite transformation and obtain the influence of energy field and interference between martensite and analyze the influence of phase field parameters on martensite. On this basis, the sensitivity and correlation degree of various parameters to the martensite transformation process are evaluated by orthogonal test. This study lays an important theoretical foundation for effectively revealing and mastering the essence of martensite transformation law. It can find effective ways to influence the martensite transformation law, obtain optimal parameters, and improve the mechanical properties of materials. Abstract : Accurate acquisition of the microscopic of the martensite transformation process is the key to obtaining the best performance of the material. The paper shows the process of martensite transformation during quenching by modeling, and the influence of material parameters on this process is also analyzed, an orthogonal test is designed to find the optimal parameters to obtain ideal microstructure of material.